Aplikasi Berbagai Komposisi dan Konsentrasi Pupuk Majemuk untuk Pembentukan Kantong pada Nepenthesx ventrata - Romy Agus Saputro; Sintho Wahyuning Ardie; . Krisantini (Departemen Agronomi dan Hortikultura, 2013)
Nepenthes is a genus of carnivorous plants in the monotypic family Nepenthaceae. The genus comprises around 130 species, numerous natural and many cultivated hybrids. Plants generally need fertilizer to promote their growth and development. However, in their original habitat Nepenthes forms pitchers under nutrition starvation condition. This study aimed at determining the effect of fertilization on the growth and pitcher formation of Nepenthesx ventrata. Experiment was conducted at Suska Nursery, Caringin, West Java, Indonesia from February until June 2011. Plants were treated with the N: P: K, 60-30-30, 32-10-10 and 10-55-10 and at different concentrations ie, 0.5, 1 and 2 g L-1. Fertilizer was applied weekly to the growing media. Weekly observations were conducted on number of leaves, plant height, time of pitchers initiation, the number of pitchers and pitcher diameter and length. Daily temperature, relative humidity and EC (electrical conductivity) of the growing media were also recorded during the experiment. The results showed that combination of fertilizer with different composition and concentration did not affect Nepenthes growth and development. Application of fertilizer resulted in smaller size pitchers compared to control plants. Future research on Nepenthes should be conducted in a longer period since Nepenthes is a slow growing plants.Keywords: Nepenthesx ventrata, fertilizer, pitcher plant